CURRENT ISSUES OF DIGITALIZATION OF THE PROCESS OF LENDING INDIVIDUALS - Abdunazarov Shahrukh Akrom ugli (American Journals, 2025)
This article analyzes the importance of digitization in the process of crediting individuals and its role in the modern banking system. Today, digital technologies are an important factor in automating banking services, increasing service speed, and creating convenience for clients. Also, the article considers the main problems of the digitalization of the lending process, in particular, issues of information security, digital inclusion, and infrastructure improvement. At the same time, foreign experiences will be analyzed, and proposals will be made to improve digital lending mechanisms in the banking system of Uzbekistan.
Keywords: Lending, individuals, banking system, information security, digital technologies.